Climate Change in international socio-economic context: regulation, socioeconomic effects and financing. Contributions of the COP21 of Paris (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
According to the work of the Intergovernmental Panel on Climate Change (IPCC) of United Nations, a rise in the global temperature of more than 2°C would have serious consequences, such as an increase in the frequency of extreme climate events. This paper examines climate change in the context of the international legal framework in recent years, including the commitments reached so far, the existing financial mechanisms to deal with climate change and COP21`s results at the Paris Summit. It also addresses mitigation and adaptation as key measures taken to reduce the impact of climate change and GHGs emissions.
Keywords: Paris Agreement; adaptation; green bonds; COP21; national designated entities; Green Climate Fund; GHGs; Kyoto; loss and damages mechanism; intended nationally determined contributions; mitigation; carbon tax